Studying history - Webster, John. C. B. (Delhi : Macmillan India Limited, 2006)
This text focuses first on the impact of the Marshall Plan on the organization of political and economic life in post-war Europe and how the plan was perceived in European public opinion. It goes on to discuss resultant political structures and the post-war economic "miracle" in Western Europe.
Includes notes.
Keywords: Studying history